EVALUASI BERJALAN PROGRAM PENYEDIAAN AIR MINUM DAN SANITASI BERBASIS MASYARAKAT - Pratama, Arif Budy; Isnanik, Ajeng Tri (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2018)
This research aims to conduct on-going evaluation on community-based clean water and sanitation program (PAMSIMAS) 2015-2018 in the Jogomulyo Village, Magelang Regency. PAMSIMAS is one of strategic government program to achieve clean and healthy communities by providing clean and drinking water services and sanitation based on community participation. Our on-going evaluation occupy six aspects as an analytical framework consist of effectiveness, efficiency, adequacy, equity, responsiveness, and appropiateness. A qualitative research with case study as research strategy was conducted to address the research aim. We triangulate both primer and secondary data to attain data source validity. Our study shows that PAMSIMAS 2015-2018 has contributed some positive results in the effort to provide clean water and sanitation services for Jogomulyo villagers. However, efficiency and resource utility aspects need to be improved to maximize the outcome of this program. There are two implications from this study. First, that government have to formulate ongoing evaluation framework since there is no on-going evaluation standard and various instrument was apllied in PAMSIMAS evaluation. Second, capacity building is necessity to build more competence management.